Educating the Concept of Al-Sabr Based on Thematic Qur'anic Exegesis to Enhance Community Mental Resilience - Sabran Kamal; Mardan Mardan; Muhsin Muhsin (Maslahah: Jurnal Pengabdian Masyarakat, 2026)
This Community Partnership Program (PKM) aimed to strengthen Islamic character education through education on the values of al-sabr (patience) from the perspective of the Qur'an. The program was implemented using a participatory approach through educational sessions, interactive lectures, discussions, and mentoring activities to enhance participants' understanding of the meaning, forms, and practical application of patience in daily life. The learning materials were developed based on a thematic interpretation of Qur'anic verses related to patience and contextualized to address current challenges in character building within educational and community settings. The results of the program indicated an improvement in participants' understanding of the concept of patience, which was no longer viewed merely as passive acceptance of hardship but also as perseverance in obeying Allah, refraining from sinful acts, and remaining steadfast in facing life's challenges. Furthermore, participants demonstrated increased awareness of the importance of patience in fostering discipline, responsibility, emotional self-control, mental resilience, and spiritual intelligence. The program contributed positively to strengthening the internalization of Islamic character values and encouraged participants to apply patience in their personal lives, families, and educational environments. Therefore, education on the values of al-sabr based on the Qur'an can serve as an effective strategy for reinforcing character education within the community.